CSUCI Distance Education Overview
CSUCI offers 2 fully online programs. They are both run through the self-support unit, Extended University. At the undergraduate level, EU at CSUCI offers a BS in Business and a BA in Psychology fully online. We also hybrid BS in Nursing degree and a fully online Masters in Nursing degree which includes two embedded certificates.The recent shift in WSCUC's definition of distance education that required institutions to request and obtain substantive change approval for all academic programs in which 50% or more of the program (units for completion of the program) could be offered through distance education, including general education components, pushed CSUCI to request review for all of our undergraduate programs in May 2022; approvals were received for all requests in June 2022. In the context of the Substantive Change review requirement for programs, WSCUC considers a distance education course to be one in which 50% or more of the instruction and interaction occurs using one or more of the technologies included in the definition of distance education, with the faculty and students being physically separate and pertains to the entire set of courses/units a student undertakes to complete the program.